Separation of Less Satisfactory Surface Active Antibiotic (Penicillin G) From Dilute Solution Using Foam Separation Method - MUKHOPADHYAY, GOUTAM; KHANAM, JASMINA (Asian Journal of Chemistry, 2010)
Penicillin-G is the drug of choice for infection caused by organisms suspectible to it. In case of streptococcal infection (like pharyngitis, scarlet fever), staphylococcus infection, pneumococcus infection, diphtheria, tetanus and gas gangrene, anthrax, actinomycosis and rat bite fever penicillin-G is widely used. Separation and purification of penicillin-G from a mixture of other components is common and essential step in pharmaceutical industry. Separation and purification of drug component from a mixture of components, separation of enantiomeric drugs mixture, separation of chemical constituents from plant source and removel of drug components from wastewater can be carried out through foam separation method. The aim of this work is to study performance criteria of separation of penicillin-G from an aqueous solution by controlling of different variables and using two type of surfactants in foam separation method. The result showed that penicillin-G can be easily separated from dilute solution of drug mixture in a short time. The influence of operatives variables including concentration of surface active agent, pH, superficial gas velocity (SGV) and recovery of drug were investigated. The optimum separation has been set as follows: concentration of surface active agent tetradecyl trimethyl ammonium bromide (2.25 mM) and dodecylamine (2.25 mM), pH 7, superficial gas velocity 0.03 cm/s, % of drug recovery was found as 84.20 and 86.78, respectively. The unique advantage of the present work relative to other reported method is the higher separation efficiency at lowest cost.